Improvement of Activity and Social Science Learning Outcomes through Teams Game Tournament Using Crossword Puzzle - Ismayenti Ismayenti; Syafri Anwar; Khairani Khairani (Fakultas Ilmu Pendidikan UNP)
This research was motivated by low activity and learning outcomes of social science sat IX.1 class in SMP Negeri 3 Sungai Geringging. Therefore it was necessary to improve learning, . The purpose of this study was to improved the activity and learning outcomes of social science through cooperative learning model, type teams game tournament by using crossword puzzle on the achievement of nineth grade students in SMP Negeri Sungai Geringging, semester 1 academic 2017/2018. The method used wasclassroom action research. The research procedure was conducted in two cycles. Each cycle consists of four stages: planning, acting, observing, and reflecting. Data collection techniques such as observation and formative tests (cognitive). Data analysis techniques used qualitative and quantitative analysis. The results was found the average percentage of the students activity in cycle 1 was 63.8% , in increased to 90.5% (very active). the average score was 73.9 in cycle 1, with percentage 65.7% or 23 students completed, the average score in cycle 2 79,3 with percentage 88,6% or 31 students completed